2015
DOI: 10.1123/jsm.2014-0283
|View full text |Cite
|
Sign up to set email alerts
|

Spectator Sport and Population Health: A Scoping Study

Abstract: This article examines the current state of research regarding the effect of spectator sport on population health. We conducted a scoping study that involved a comprehensive search of published and gray literature between 1990 and 2014, and identified 135 studies empirically examining the effect of spectator sport on population health. A frequency analysis shows that there is a paucity of studies on this topic published in sport management journals. A thematic analysis further reveals that the reviewed studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
83
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(86 citation statements)
references
References 140 publications
0
83
0
3
Order By: Relevance
“…Consistent with Arksey and O'Malley and previous scoping reviews within the sport management domain (Inoue et al, 2015), a frequency and thematic analysis was conducted.…”
Section: Collating Summarizing and Reporting Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with Arksey and O'Malley and previous scoping reviews within the sport management domain (Inoue et al, 2015), a frequency and thematic analysis was conducted.…”
Section: Collating Summarizing and Reporting Resultsmentioning
confidence: 99%
“…They are increasingly popular in other domains such as medicine and health (e.g., Pham et al 2014), but so far remain uncommon within the sport management literature (for exception see Inoue, Berg, & Chelladurai, 2015). The purpose of a scoping review is to examine the extent and range of research in an area, determine the value of further reviews, summarize and disseminate research findings, and identify research gaps in the existing literature (Arskey & O'Malley, 2005).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst valuable, this perspective focuses largely on the perspective of sport organisations, which detracts attention from the individual-level benefits of spectating. Inoue, Berg, and Chelladurai (2015) illustrate this oversight, outlining a paucity of research attention dedicated to the relationship between sport consumption, and health and well-being. Furthermore, Inoue et al (2015) note that only 9% of studies exploring this relationship are located in sport management journals, prompting a call for more research in this emerging area.…”
mentioning
confidence: 99%
“…Existing spectator research, however, focuses on health and physical domains of well-being, devoting less attention to psychological states. A review of 135 relevant spectator manuscripts published between 1990 and 2014 demonstrated that health (47%) and physical well-being (24%) are well researched; however, domains of mental (20%) and social well-being (15%) receive much less attention (Inoue et al, 2015). Despite this weakness, researchers have established that sport spectating and psychological health are conceptually (Wann, 2006c) and empirically related (e.g., Branscombe & Wann, 1991;Theodorakis, Wann, Nassis, & Luellen, 2012;Wann, 2006a;Wann, Dimmock, & Grove, 2003;Wann, Keenan, & Page, 2009;Wann & Pierce, 2005; Wann, Rogers, Dooley, & Foley, 2011;Wann, Waddill, Polk, & Weaver, 2011; Wann & EXPLORING PERMA IN SPECTATOR SPORT 4 Weaver, 2009).…”
mentioning
confidence: 99%